#TITLE_ALTERNATIVE# - ARI KUSUMA (NIM : 22310002), ISTIQOMAH
Accurate and detail of subsurface imaging is the intention of seismic data processing. However, there were limitations on seismic data and the undulation event reflectors make the conventional processing not optimal, thus the result can't image the subsurface correctly. To solve this problem, a better method than conventional method is needed. One of the method is Zero Offset Common Reflection Surface (ZO CRS) Stack. ZO CRS Stack did not only use VNMO like in conventional method, but also use CRS stacking operator which can determined the best fits for the actual reflector. In this thesis, conventional seismic data processing method will be compared with CRS method to analyze how well CRS method can improve the subsurface imaging. In this thesis used real data land by short far-offset, has conflicting dip and fault. The data processed using conventional and CRS method until the stage of Prestack Time Migration. Furthermore, stack data resulted from Prestack Time Migration (PSTM) was applied Acoustic Impedance Inversion (AI) and then studied how good inversion section from CRS data than conventional data. From the comparison between two methods, the results of CRS-Stack method can provide seismic section which is better than conventional method so the interpretation process can be easier and more accurate.